PENGARUH ARUS KAS OPERASI, MODAL KERJA DAN LIKUIDITAS TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017–2020 - Silalahi, Esli; Lumbanbatu, Arni D.K. (Jurnal Riset Akuntansi & Keuangan, 2023)
This study aims to analyze the effect of operating cash flow, working capital (cash turnover) and liquidity (Current Ratio) on stock returns in Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2017-2020 . The population in this study were 175 manufacturing companies. The sampling technique used was purposive sampling based on certain criteria, in order to obtain a sample of 34 companies with a research period of 4 years. The data analysis technique used is multiple linear regression analysis. Hypothesis testing uses the t test and F test with a significance level of 5%.The results of the t-test study show that operating cash flow has a positive and significant effect on stock returns, working capital (cash turnover) has a positive and significant effect on stock returns, and liquidity (current ratio) has a positive and significant effect on stock returns in manufacturing companies listed on Indonesia Stock Exchange Period 2017-2020.The results of the F test show that operating cash flow, working capital (cash turnover) and liquidity (current ratio) have a positive and significant effect on stock returns in manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020.